Atypical Multiple Sclerosis Lesions or Progressive Multifocal Leukoencephalopathy Lesions: That Is the Question - Stefania Federica De Mercanti MD, PhD; Dario Gned MD; Manuela Matta MD; Marco Iudicello MD; Emanuele Franchin MD; Marinella Clerico MD, PhD (SAGE Publishing, 2020)
Progressive multifocal leukoencephalopathy (PML) is a serious infective disease of the central nervous system that may occur in case of severe immunosuppression or after some treatment for multiple sclerosis (MS) with natalizumab, dimethyl fumarate, and fingolimod. In these case reports, we highlight the importance of differential diagnosis between PML and MS lesions in order to provide rapidly the best treatment option, by discussing the finding of brain (magnetic resonance imaging) MRI suggestive for PML in 2 MS patients, one treated with dimethyl fumarate and the other during natalizumab withdrawal. In both cases, although brain MRI was highly suggestive for PML, the detection of John Cunningham virus-DNA copies in cerebrospinal fluid resulted in negative result. These case reports illustrate the diagnostic process in case of suspected PML, as both patients were diagnosed with suspected PML during a routine brain MRI control, and highlights the importance of providing a strict brain MRI follow-up during dimethyl fumarate treatment, although only a few cases of PML during this therapy have been detected, and during natalizumab suspension phase. In clinical practice, in case of a radiologically suspected case of PML, although not confirmed by the cerebrospinal fluid analysis, the best approach could be to perform a close radiological and clinical monitoring before starting a new MS therapy.